2000
DOI: 10.1034/j.1600-0404.2000.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Galantamine is an allosterically potentiating ligand of the human α4/β2 nAChR

Abstract: Galantamine (ReminylTM) is a novel drug treatment for mild to moderate Alzheimer's disease (AD). Originally established as a reversible inhibitor of the acetylcholine‐degrading enzyme acetylcholinesterase (AChE), galantamine also acts as an allosterically potentiating ligand (APL) on nicotinic acetylcholine receptors (nAChR). Having previously established this second mode of action on nAChRs from murine brain, we demonstrate here the same action of galantamine on the most abundant nAChR in the human brain, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
108
1
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 30 publications
4
108
1
3
Order By: Relevance
“…al., 1985) was the finding that physostigmine-induced inhibition of ␣4␤4 and ␣4␤2 nAChR activity was voltage dependent . As we have shown previously for galantamine (Schrattenholz et al, 1996;Samochocki et al, 2000), physostigmineinduced potentiation of nAChR activity was only evident at subsaturating concentrations of classical agonists . Based on the finding that the potentiating effect of physostigmine faded away as the agonist concentration was increased and that physostigmine displaced the binding of the classical nicotinic agonist epibatidine from ␣4␤4 nAChRs ectopically expressed in oocytes, Zwart and collaborators (2000) concluded that the potentiating action of physostigmine is the result of its interaction with the ACh-recognition sites on the nAChRs.…”
Section: Exogenous Unconventional Nachr Ligands That Modulate Receptsupporting
confidence: 80%
See 4 more Smart Citations
“…al., 1985) was the finding that physostigmine-induced inhibition of ␣4␤4 and ␣4␤2 nAChR activity was voltage dependent . As we have shown previously for galantamine (Schrattenholz et al, 1996;Samochocki et al, 2000), physostigmineinduced potentiation of nAChR activity was only evident at subsaturating concentrations of classical agonists . Based on the finding that the potentiating effect of physostigmine faded away as the agonist concentration was increased and that physostigmine displaced the binding of the classical nicotinic agonist epibatidine from ␣4␤4 nAChRs ectopically expressed in oocytes, Zwart and collaborators (2000) concluded that the potentiating action of physostigmine is the result of its interaction with the ACh-recognition sites on the nAChRs.…”
Section: Exogenous Unconventional Nachr Ligands That Modulate Receptsupporting
confidence: 80%
“…These effects can be detected as early as 30 s after beginning the perfusion of the slices with galantamine-containing artificial cerebrospinal fluid (ACSF). In contrast, cholinesterase inhibitors devoid of nicotinic APL action, including methamidophos, donepezil, and rivastigimine (Samochocki et al, 2000), cause no significant changes in evoked EPSCs or IPSCs in hippocampal slices (Santos et al, 2002). Numerous lines of evidence demonstrated that facilitation of glutamatergic and GABAergic transmissions by galantamine cannot be accounted for by changes in the electrical properties of the neurons or in the activity of postsynaptic glutamate or GABA A receptors.…”
Section: Therapeutic Significance Of Nicotinic Aplsmentioning
confidence: 99%
See 3 more Smart Citations